Analysis of oceanic waters and sediments - Crompton, T. R.
"The presence of concentrations of organic substances and cations in seawater is a matter of increasing concern to the water industry, environmentalists and the general public alike. It poses a threat of possible health hazards for humans, fish and crustacea. Until fairly recently, the analysis of seawater was limited to a number of major constituents such as chloride and alkalinity. Insufficient attention was given to the analysis of sediments. Analysis of Oceanic Waters and Sediments draws attention to the methods available for analysing sediments in seawater. It covers classical methods as well as the most advanced and recently introduced physical techniques. It also discusses the sensitivities and limitations of the methods. The book is comprised of two major components. The first is a review of the occurrence of organic compounds and cations as well as examples of pollution by these substances in the ocean. The second is concerned with determination of the concentrations of organic compounds and metals, including an in-depth examination of the most sensitive analytical methods that are available and necessary for detecting them due to their low concentrations in the ocean. A detailed exploration of the largely overlooked area of oceanic sediment analysis, this book is of high interest for all professionals in the water industry, from river management to fish industries, sewage effluent treatment and disposal, land drainage and water supply. Its scope also applies to agriculturalists, chemists, biologists, toxicologists, public health workers and public analysts"--